Sequence variations in DNA repair gene XPC is associated with lung cancer risk in a Chinese population: a case-control study - Jin Li; Liu Yanhong; Chen Feng; Huo Xiang; Jing Guangfu; Yang Lin; Chen Weihong; Liu Hongliang; Wang Ying; Ma Hongxia; Qian Ji; Yuan Wentao; et al. (BMC Cancer, 2007)
Abstract Background The nucleotide excision repair (NER) protein, xeroderma pigmentosum C (XPC), participates in recognizing DNA lesions and initiating DNA repair in response to DNA damage. Because mutations in XPC cause a high risk of cancer in XP patients, we hypothesized that inherited sequence variations in XPC may alter DNA repair and thus susceptibility to cancer. Methods In this hospital-based case-control study, we investigated five XPC tagging, common single nucleotide polymorphisms (tagging SNPs) in 1,010 patients with newly diagnosed lung cancer and 1,011 matched cancer free controls in a Chinese population. Results In individual tagging SNP analysis, we found that rs3731055AG+AA variant genotypes were associated with a significantly decreased risk of lung adenocarcinoma [adjusted odds ratio (OR), 0.71; 95% confidence interval (CI), 0.56–0.90] but an increased risk of small cell carcinomas [adjusted OR, 1.79; 95% CI, 1.05–3.07]. Furthermore, we found that haplotype ACCCA was associated with a decreased risk of lung adenocarcinoma [OR, 0.78; 95% CI, 0.62–0.97] but an increased risk of small cell carcinomas [OR, 1.68; 95% CI, 1.04–2.71], which reflected the presence of rs3731055A allele in this haplotype. Further stratified analysis revealed that the protective effect of rs3731055AG+AA on risk of lung adenocarcinoma was more evident among young subjects (age ≤ 60) and never smokers. Conclusion These results suggest that inherited sequence variations in XPC may modulate risk of lung cancer, especially lung adenocarcinoma, in Chinese populations. However, these findings need to be verified in larger confirmatory studies with more comprehensively selected tagging SNPs.